Closure Policy when Bank Inspection Can Be Manipulated - Calveras, Aleix (Review of Finance, 2003)
Abstract This paper analyzes inspection and closure policies of a bank, and the strategic reaction of its managers/shareholders when they can (costly) manipulate the information available to the regulator. We derive optimal intervention policy, and analyze its effect on managerial strategies. Regulatory intervention may induce shareholders to manipulate the information available to the regulator in order to avoid intervention and closure, and we find that these incentives to manipulate information may increase with tighter capital requirements. Finally we show that, in order to avoid manipulation by the banker, some degree of forbearance in closure may be ex ante optimal. JEL classification codes: G21, G28